STUDY OF FASTING PLASMA GLUCOSE AND LIPID PROFILE IN POSTMENOPAUSAL WOMEN - FARHA ALI; BINDRA, MANINDER (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objectives: The study was designed to determine fasting plasma glucose (FPG) and lipid profiles in postmenopausal women. Methods: 200 postmenopausal women were enrolled for the study and were compared to 100 normal healthy women of the same age from the Outdoor Patient Department of LN Medical College and research center of Bhopal city. Those fulfilling inclusion and exclusion criteria were enrolled for the study and the blood samples were analyzed for lipid profile and FPG. Results: Significant higher concentrations of total cholesterol (p<0.001), triglyceride (p<0.001), low-density lipoprotein (LDL) (p<0.001), very LDLs (p<0.001), and FPG (p<0.001) were demonstrated in postmenopausal women when compared with normal healthy women. A significantly lower concentration of high-density lipoprotein (p<0.001) was demonstrated in postmenopausal women when compared with normal healthy women. Conclusion: Menopausal transition and the related changes in the hormonal milieu (e.g., decreased systemic estradiol (E2) levels) are linked with adverse changes in several indicators of metabolic health. For instance, during the menopausal transition elevated blood glucose levels and adverse changes in serum lipids have been reported.